Investigating the Effect of Semantic Broadening and Narrowing on Ecological Terminologies (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
This study investigates 20 ecological terminologies to assess the impact of semantic broadening and narrowing, and analyzing how such changes shape systematic communication, public perception, and policy formulation. It adopts MAK Halliday’s systemic functional theory to analyze the secondary data using a qualitative analytical approach to examine the semantic change of broadening and narrowing in a few ecological terminologies. Through corpus analysis and discourse evaluation, we identify patterns of semantic shift in key ecological terms such as “environment”, “climate justice”, “biodegradables”, “green”, “biodiversity,” etc., and assess their implications for clarity and conceptual coherence in ecological research. The findings reveal that most familiar ecological terminologies undergo broadening compared to narrowing. While certain word formation processes, such as broadening, can undergo semantic narrowing, it risks ambiguity, whereas narrowing fosters precision but may restrict contextual relevance. The study underscores the need for balanced lexical evolution to maintain terminological rigor in ecological science while accommodating dynamic environmental discourse.
Keywords: Semantic Change; ecological terminologies; broadening; narrowing; environmental discourses